Combined pancreaticoduodenectomy and colon resection for locally advanced peri‐ampullary tumours: analysis of peri‐operative morbidity and mortality. Issue 9 (18th April 2014) - Temple, Sara J.; Kim, Peter T.W.; Serrano, Pablo E.; Kagedan, Daniel; Cleary, Sean P.; Moulton, Carol‐Anne; McGilvray, Ian D.; Gallinger, Steven; Greig, Paul D.; Wei, Alice C.
Abstract Background Combined pancreaticoduodenectomy (PD) and colonic resection may be necessary to achieve an R0 resection of peri‐ampullary tumours. The aim of this study was to examine the morbidity and mortality associated with this procedure. Methods A retrospective cohort study was performed comparing 607 patients who underwent a standard pancreaticoduodenectomy (S‐PD) to 28 patients who had a concomitant colon resection and PD (PD‐colon) over a 10‐year period at an academic centre. Results Patients in the PD‐colon group were more likely to have received neoadjuvant chemotherapy ± radiation (3/28, 11% versus 14/607, 2%, P = 0.024). Operative time was also longer (530 versus 410 min, P < 0.001) and they were more likely to have had portal vein resections (9/28, 32% versus 76/607, 13%, P = 0.007). There was no difference in the intra‐operative blood loss, length of stay, or overall complication rates. The PD‐colon group had a higher rate of severe post‐operative bleeding (4/28, 11% versus 8/607, 1%, P = 0.002). The post‐operative mortality rates for the PD‐colon and PD groups were 2/28 (7%) and 8/607 (1%), respectively (P = 0.068). Conclusions PD‐colon has an acceptable risk of peri‐operative morbidity compared with S‐PD in well‐selected patients.